Cabergoline Induced Supraventricular Tachycardia with QT Prolongation - Menon, Vineetha Bharathan; Gaddipati, Bhanuvaishnavi; R, Venkatesh C; Pereira, Pratibha; Gowdappa, Hathur Basavanna; Ramesh, Madhan (Indian Journal of Pharmacy Practice)
Background: Cabergoline is commonly known to cause valvular disorders. Cases of supraventricular tachycardia with QT prolongation are seen, albeit, extremely rare. Aim: We report a case of supraventricular tachycardia with QT prolongation presumed secondary to cabergoline use. Clinical Details: A 30-year-old post-partal female complained of palpitation and syncope after two days of cabergoline usage. Her past medical history was insignificant. Electrocardiogram showed QT prolongation of 489 ms. Based on her presentation, we presume that the patient’s condition was the result of cabergoline. Outcomes: Causality assessment was suggestive of a probable relationship between the patient’s symptoms and her use of cabergoline. Symptoms improved significantly after the offending drug was withdrawn with an objective reduction in QTc. Conclusion: Electrocardiogram should be monitored in individuals receiving more than one QT prolonging medication or with symptoms of arrhythmia or are at high risk of QT prolongation/Torsades de Pointes.
Keywords: Adverse Effects; Arrhythmia; Cabergoline; QT Prolongation; Supraventricular Tachycardia; Torsades de Pointes